Contributions of Sustainable Tourist Behavior in Food Events to the Cultural Identity of Destinations - María-Dolores Sánchez-Sánchez; Carmen de Pablos-Heredero; José Luis Montes-Botella (Tourism and Hospitality)
Gastronomic event tourism is an emerging phenomenon that attracts an increasing number of tourists seeking a memorable gastronomic experience based on its cultural uniqueness, highlighting the need to understand the behavior of this tourism demand. This study proposes a model to determine the importance of food tourism events in developing the cultural identity of tourist destinations by analyzing the tourist experience concerning their motivation, satisfaction, and loyalty, understood as variables of sustainable tourism behavior. The hypotheses in the model have been tested using non-linear structural equations modeling (SEM), estimated with data from the Resident Tourism Survey of the National Statistics Institute (NSI), on domestic demand for value-added gastronomic tourism in Spain. The data analyzed covers the period from January 2019 to December 2022 (n = 3483). The results show a significant relationship between the variables influencing overall tourist satisfaction with gastronomic events and tourist loyalty. This research provides knowledge on the behavior of gastronomically motivated tourists with practical implications for destinations, aimed at improving decision-making in the definition of tourism strategies, focusing on the preservation and enhancement of their gastronomic offer as a cultural identity through the offer of food events.